(3OGeZ GdChgGe aj TQM cJGH QjGVI GdCagGe aj dWja GdcdGes - (3GdegOi HGddg CMeO Hf jMji Hf GdeQJVis; (3GdegOj dOjf Gddg , CMeO Hf jMji Hf GdeQJVj Hf eaVd Hf efUhQ GdMSfj, GdegOj dOjf Gddg,J (B840 (3g` s ((3EHQGgje Hf YHO Gddg GdfLje s)
(3ChdgG (B:s
(3hjfHZi Cf fJcde ai aUdjf CMOgeG ai JMbjb gPg GdJSejI dgPG GdYde heLGRjJgG , hGdKGfi ai aGFOI gPG GdYde hHjGf s
(3BNQgG (B:s
(3aUGQ cCfg de jbY QCSkG , hHgPg GdLedI Je TQM QjGVI GdCagGe ai dWja GdcdGe Ke bGd hcGf GdaQGZ ef JCdja gPG GdTQM s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3Ydi MhGTjgG JYdjbGJ s
(3HOGNdgG ChQGb HNW eZGjQ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdeYGQa GdYGeIs